Association of Muscle Fibers with Histopathology in Doughnut Specimens Following Stapled Hemorrhoidopexy and Their Impacts on Postoperative Outcomes - Narayanaswamy, Chetty Y. V.; Sreevathsa, M. R.; Chowdari, G. Akhil; Rao, Koteshwara (The Surgery Journal, 2022)
Background Stapled hemorrhoidopexy is widely practiced worldwide since its introduction to the world of proctology and replaced conventional hemorrhoidectomy in treating hemorrhoids. The technique of executing the procedure dictates the outcomes and complications. Here, we attempted to establish the cause of postoperative complications and attributed them to the presence of muscle of fibers in the excised doughnut specimens.Materials and Methods A prospective observational analysis of histopathological specimens obtained from patients who underwent stapled hemorrhoidopexy using procedure for prolapse and hemorrhoids-03 circular staplers in the department of surgery of a tertiary care hospital in southern India was performed, and the correlation between the presence or absence of muscle fibers in the specimens and postoperative complications was evaluated. The patients were followed up for 12 months after the procedure.Results In this study, 155 patients, including 54, 91, and 10 patients with Grade 2, Grade 3, and Grade 4 hemorrhoids, respectively, were included. Group A consisted of 19 patients with muscle fibers on the specimens, whereas Group B consisted of 139 patients without muscle fibers on the specimens. Early complications within 7 days after the procedure were as follows: 21 and 0.7% of the patients in Groups A and B, respectively, presented with postoperative pain with a visual analog scale score of more than 4; 47 and 6% of the patients in Groups A and B, respectively, presented with urinary retention; 26 and 2% of the patients in Groups A and B, respectively, presented with bleeding; and 21 and 2.9% of the patients in Groups A and B, respectively, presented with fecal urgency. A significant association was found between the presence of muscle fibers and early complications (p < 0.001). Late complications, such as proctalgia and bleeding, accounting for 36.8 and 6.6% in Groups A and B, respectively, were significantly associated with the presence of muscle fibers in histopathology (p < 0.001). Meanwhile, other late complications, such as incontinence, stenosis, and recurrence, exhibited no association (p > 0.05).Conclusion The technique in taking purse-string sutures and the depth of the suture bite above the dentate line carry the utmost importance in preventing postoperative complications. Therefore, surgeons should refine their technique of appropriate depth to avoid incorporation of muscle fibers while executing the procedure.
Keywords: anus; hemorrhoids; stapled hemorrhoidopexy